The Effect of Statistical Fluctuations on the Measurement of the Total Energy and Multiplicity of y Rays Following Deep-Inelastic Reactions - Pacheco, A. J.; Moretto, L. G. (Springer-Verlag, 1982)
Fil: Pacheco, A. J. Comisión Nacional de Energía Atómica; Argentina